Visualization of Chronic Myocardial Infarction Using the Intravascular Contrast Agent MS-325 (Gadofosveset) in Patients - Thomas Thouet; Bernhard Schnackenburg; Thomas Kokocinski; Eckart Fleck; Eike Nagel; Sebastian Kelle (The Scientific World Journal)
Aims. The aim of this study was to evaluate the potential of visualizing chronic myocardial infarction in patients using the intravascular CA MS-325 (gadofosveset, EPIX Pharmaceuticals, Mass, USA). Methods. Nine patients were enrolled in a clinical phase II multicenter trial for MRCA and perfusion imaging using MS-325. They had objective evidence of chronic myocardial infarction as visualized by previously performed late gadolinium (Gd) enhancement imaging (LGE) with a conventional extracellular Gd-DTPA CA (Magnevist, Bayer Healthcare, Germany, 0.2 mmol/kg/body weight) serving as reference standard. A prepulse-optimized LGE study was performed immediately and at several time points after injection of MS-325 (0.05 mmol/kg/body weight). The number and localization of segments demonstrating LGE with MS-325 as well as signal intensities were compared with the reference standard (Gd-DTPA). Results. Using MS-325, LGE could be detected at every time point in all 9 patients. The accuracy of LGE with MS-325 as compared to LGE with Gd-DTPA was highest 54±4 minutes after contrast injection, resulting in a sensitivity of 84% with a specificity of 98%. Conclusion. The intravascular CA MS-325 has the potential to visualize chronic myocardial infarction. However, in comparison with Gd-DTPA, the transmural extent and the number of segments are smaller.